SEX DETERMINATION IN INDONESIAN PUFFERFISH Tetraodon palembangensis Bleeker, 1852: IMPLICATION FOR AQUACULTURE AND CONSERVATION - Media Fitri Isma Nugraha; I Wayan Subamia; Sudarto Sudarto; Wahyu Purbowasito (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
The study was based on eight specimens from a single population of Palembang pufferfish. We used a comprehensive approach comprise behavioral record, the Random Amplified Polymorphism DNA technique, exteriorly genital observation and the description of morphological coloration distinctive to recognize gender. Annotation from captivity has yielded that two genders in couple were possessed the prominent social respond in shoaling-fidelity. When the gonadal process has been released by maternal part, eggs and offspring were kept by male and there is no tolerable contact of female were given, here the female has become more cannibalism. Male adult has more brown-blackish and occasionally more flukes-dark on the half upper horizontal body it has less towering bulk and only has one genitalial hole. Female furthermore is recognizable with the present hight-bulk and has more yellow overall flukes in coloration and widely bright yellowish-dark from abdomental part to the edge of middle half of the body. Contrary, female has two genitalian holes. RAPD also has confirmed a concordance linkage what we are previously expected. We found an important mutation 176 bp for both gender. Among the scaffold obtained, scaffold 33 is a common scaffold identified within T. palembangensis and Takifugu, it has a sufficient score bit of 36.2 with a length of nucleotide 1,758,880 bp. Moreover, this scaffold is the result from primer OPP-19 in the female of T. palembangensis, we thus can finally distinguish their sex status. The scaffold 33 might relate to the gene SOX. Our attempt may hatch a new horizon for institutional developers, aquarist and conservationist in case of surety for sustainable natural population and to ensure their stock for consumption and trading ornament requirement.